Seaside Goldenrod, Solidago sempervirens - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Seaside goldenrod is highly tolerant of both saline soils and salt spray and is usually found on beach dunes, tidal marshes, and disturbed areas throughout coastal areas from Mexico North to Maine and on islands in the Bahamas. It is a prolific flower- and seed-producer. It attracts many pollinators, including birds, native bees, honey bees, butterflies (especially Monarch butterflies), and beneficial insects. The flowers are an important food/energy source for fall migrating monarch butterflies traveling the Atlantic coastal flyway (Sheahan 2014). https://edis.ifas.ufl.edu/sg185